The role of breast reconstruction choice on body image patient‐reported outcomes at four years post‐mastectomy for breast cancer: A longitudinal prospective cohort study. Issue 1 (8th September 2021) - Dempsey, Kathy; Mathieu, Erin; Brennan, Meagan; Snook, Kylie; Hoffman, Julia; Campbell, Ian; Scarlet, Jenni; Flay, Heather; Wong, April Z. H.; Boyle, Frances; King, Madeleine; Spillane, Andrew
Abstract: Objectives: To examine the impact of breast reconstruction on women's perceptions of body image over time and to assess the influence of sociodemographic variables on body image. Methods: A prospective, longitudinal cohort study, using validated breast cancer‐specific questionnaires, to compare patient‐reported outcomes in women choosing immediate ( n = 61), delayed ( n = 16) or no ( n = 23) breast reconstruction. Results: One hundred women completed baseline questionnaires that included items on body image; 30 women completed all four annual follow‐up sets, while 20 women completed baseline only. The three groups were well matched at baseline and similar trajectories in body image measures were identified over 48 months in all groups. At 12 months post‐mastectomy, significant changes were seen in eight of the 10 subscales; this reduced to seven subscales at 24 months and four at 36 months. By 48 months, only three subscales remained significantly different to baseline scores: women remained less vulnerable and had fewer limitations (improved outcomes); the one worse outcome was persistently higher levels of arm concern. Three of the sociodemographic variables (health insurance, age and employment status) showed significant inter‐group differences at some time points. Conclusion: These findings suggest women recover from the negative impact of mastectomy on body image within four years of surgery, whether they have immediate, delayed or no reconstruction. Our results provide some indirect evidence that having a choice of BR options is important, regardless of the choice made. Four years appears to be a suitable follow‐up period for future studies in this area.